SPE Annual Technical Conference and Exhibition 2013
DOI: 10.2118/166365-ms
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Decline Curve Analysis Methods with Analytical Models in Unconventional Plays

Abstract: Unconventional plays have moved to the forefront of the energy industry in the U.S. over the last five years due to advancements in technology and the overall abundance of producible hydrocarbons discovered near existing infrastructure. In the present economic climate, there is an increased interest in liquid rich plays, and because of the relatively limited historical production data available for these resources, there is a lot of industry discussion regarding future decline performance and estimated ultimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Kanfar and Wattenbarger [12] showed that the Duong model is more accurate for linear flows and bilinear-linear flows. Meyet et al [28] showed that the EURs determined with PLE and Duong model vary the least with respect to the length of production history for all wells among all of the DCA methods in their study, and other DCA methods tend to converge towards the modified Duong model and PLE model. Furthermore, the Duong model tends to provide the most conservative results.…”
Section: Duong Modelmentioning
confidence: 88%
See 4 more Smart Citations
“…Kanfar and Wattenbarger [12] showed that the Duong model is more accurate for linear flows and bilinear-linear flows. Meyet et al [28] showed that the EURs determined with PLE and Duong model vary the least with respect to the length of production history for all wells among all of the DCA methods in their study, and other DCA methods tend to converge towards the modified Duong model and PLE model. Furthermore, the Duong model tends to provide the most conservative results.…”
Section: Duong Modelmentioning
confidence: 88%
“…Zuo et al [35] discovered that, for shale gas wells in the Fayetteville formation, the DCA parameters are all within a certain small range. For example, for Fayetteville shale, parameter α defined in Equation (28) lies in the range from 0.65 to 0.75, which indicates that this parameter might have some relationship with the physical parameters. Zhang et al [40] showed that some recommended empirical coefficients can be determined for specific shale formations such as Eagle Ford, which may help, particularly in the early stages of development when little production data are available.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations